Police Officers’ and Victim Advocates’ Perceptions of the Lethality Assessment Program - Dutton, Leila B. (Criminal justice policy review, 2019)
This study is a preliminary assessment of police officers’ and victim advocates’ experiences with and perceptions of the Lethality Assessment Program (LAP), a program involving the collaboration between police departments and domestic violence (DV) agencies designed to prevent fatal and serious DV. Participants included 168 officers from 22 police departments and 63 advocates from 10 DV agencies. Results from online surveys indicated that officers and advocates had favorable perceptions of one another. Officers found the LAP to be less effective as a tool to deal with DV cases than advocates. Analysis of qualitative data revealed that officers and advocates identified a number of positive by-products of the LAP, but officers cited more negative by-products than advocates. Recommendations for policy and future research are provided.